2019
DOI: 10.1155/2019/9417048
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine and Methadone as Opioid Maintenance Treatments for Heroin-Addicted Patients Induce Oxidative Stress in Blood

Abstract: Buprenorphine and methadone are two substances widely used in the substitution treatment of patients who are addicted to opioids. Although it is known that they partly act efficiently towards this direction, there is no evidence regarding their effects on the redox status of patients, a mechanism that could potentially improve their action. Therefore, the aim of the present investigation was to examine the impact of buprenorphine and methadone, which are administered as substitutes to heroin-dependent patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…There is conflicting evidence as to whether opioids induce oxidative stress. For example, there is compelling evidence that morphine, buprenorphine and methadone can both increase or decrease oxidative stress depending on the circumstances and experimental conditions ( Lee et al, 2004 ; Almeida et al, 2014 ; Motaghinejad et al, 2015 ; Skrabalova et al, 2018 ; Leventelis et al, 2019 ). In contrast, the available evidence suggested that fentanyl and analogues either reduce ( Kim et al, 2017 ) or have no effect ( Krumholz et al, 1993 ; Jaeger et al, 1998 ) on oxidative stress although there is a report that a high-dose remifentanil increases myocardial oxidative stress and compromises remifentanil infarct-sparing effects in rats ( Mei et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is conflicting evidence as to whether opioids induce oxidative stress. For example, there is compelling evidence that morphine, buprenorphine and methadone can both increase or decrease oxidative stress depending on the circumstances and experimental conditions ( Lee et al, 2004 ; Almeida et al, 2014 ; Motaghinejad et al, 2015 ; Skrabalova et al, 2018 ; Leventelis et al, 2019 ). In contrast, the available evidence suggested that fentanyl and analogues either reduce ( Kim et al, 2017 ) or have no effect ( Krumholz et al, 1993 ; Jaeger et al, 1998 ) on oxidative stress although there is a report that a high-dose remifentanil increases myocardial oxidative stress and compromises remifentanil infarct-sparing effects in rats ( Mei et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, there is no real consensus as to whether opioids induce oxidative stress. For example, morphine, buprenorphine and methadone can increase or decrease oxidative stress depending on the experimental conditions ( Lee et al, 2004 ; Almeida et al, 2014 ; Motaghinejad et al, 2015 ; Skrabalova et al, 2018 ; Leventelis et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This effect has been demonstrated in morphine-addicted rodents [ 3 , 4 , 5 , 6 ], in morphine-addicted human beings (reviewed in [ 5 , 6 , 7 ]), and the mechanism elucidated in rodent [ 8 ] and human [ 9 , 10 ] hepatocytes at clinically-relevant concentrations of opioids. The loss of glutathione activity extends to blood serum [ 10 , 11 ] and is also found in patients being treated with methadone and buprenorphine [ 12 ]. Loss of neurons associated with glutathione depletion has also been reported in rodents treated with morphine or heroin [ 13 , 14 , 15 , 16 ] but the evidence for equivalent depletion in human brains from opioid abusers is mixed, with one group reporting significant depletion [ 17 , 18 ] and another reporting none [ 19 ].…”
Section: Introductionmentioning
confidence: 99%